Implementing Outcome-Oriented Study Programmes at University: The Challenge of Academic Culture - Jenert, Tobias (Zeitschrift für Hochschulentwicklung)
In recent years, the design of study programmes in Higher Education (HE) has been given considerable attention by HE practitioners and researchers. Today, a sound body of concepts and experiences on different realisations of Bologna-conforming study programmes is available. The same, however, does not hold true for questions concerning the processes of implementing and further developing programmes. This paper investigates the challenges related with implementation, particularly at universities. A first aim is to understand the specifics of academic culture and their significance for programme implementation and development. Elaborating on this analysis, a second aim is to outline the role of educational developers in this process, as well as the necessary competencies to perform such a role.
Keywords: Programmentwicklung; Studienprogramme; program development; educational development; academic culture; disciplinary culture

Constitutions and Social Networks - Mauleon, Ana; Röhl, Nils; Vannetelbosch, Vincent
The objective of this paper is to analyze the formation of group structures where individuals are allowed to engage in several groups at the same time. These structures are interpreted here as social networks. Each of the groups is supposed to have specific rules or constitutions governing which members may join or leave it. A social network is then considered to be stable if none of the groups is altered any more. Given this framework, we not only analyze which influence the constitutions have on network formation but we also provide requirements under which stable networks are induced for sure. Furthermore, by embedding many-to-many matchings into our setting, we apply our model to job markets with labor unions. To some extent the unions may provide job guarantees and, therefore, have influence on the stability of the job market.

Conceptual Model and Economic Experiments to Explain Nonpersistence and Enable Mechanism Designs Fosterin Behavioral Change - Mir Djawadi, Behnud; Fahr, Rene; Turk, Florian (Value in Health)
BackgroundMedical nonpersistence is a worldwide problem of striking magnitude. Although many fields of studies including epidemiology, sociology, and psychology try to identify determinants for medical nonpersistence, comprehensive research to explain medical nonpersistence from an economics perspective is rather scarce.ObjectivesThe aim of the study was to develop a conceptual framework that augments standard economic choice theory with psychological concepts of behavioral economics to understand how patients’ preferences for discontinuing with therapy arise over the course of the medical treatment. The availability of such a framework allows the targeted design of mechanisms for intervention strategies.MethodsOur conceptual framework models the patient as an active economic agent who evaluates the benefits and costs for continuing with therapy. We argue that a combination of loss aversion and mental accounting operations explains why patients discontinue with therapy at a specific point in time. We designed a randomized laboratory economic experiment with a student subject pool to investigate the behavioral predictions.ResultsSubjects continue with therapy as long as experienced utility losses have to be compensated. As soon as previous losses are evened out, subjects perceive the marginal benefit of persistence lower than in the beginning of the treatment. Consequently, subjects start to discontinue with therapy.ConclusionsOur results highlight that concepts of behavioral economics capture the dynamic structure of medical nonpersistence better than does standard economic choice theory. We recommend that behavioral economics should be a mandatory part of the development of possible intervention strategies aimed at improving patients’ compliance and persistence behavior.

Competitive outcomes and the inner core of NTU market games - Brangewitz, Sonja; Gamp, Jan-Philip (Economic Theory)
We consider the inner core as a solution concept for cooperative games with non-transferable utility (NTU) and its relationship to payoffs of competitive equilibria of markets that are induced by NTU games. An NTU game is an NTU market game if there exists a market such that the set of utility allocations a coalition can achieve in the market coincides with the set of utility allocations the coalition can achieve in the game. In this paper, we introduce a new construction of a market based on a closed subset of the inner core which satisfies a strict positive separability. We show that the constructed market represents the NTU game and, further, has the given closed set as the set of payoff vectors of competitive equilibria. It turns out that this market is not uniquely determined, and thus, we obtain a class of markets. Our results generalize those relating to competitive outcomes of NTU market games in the literature.

Developing study programs as a continuous task-the role of educational developers - Brahm, Taiga; Zellweger, Franziska; Jenert, Tobias; Thomann, Geri
Abstract Summary: Study programs are currently receiving more attention in Europe. In consequence, it can be observed that the roles of program development and management are professionalized. In the proposed round table, we would like to discuss the role of educational developers to support this professionalization via measures of training and process support in the light of recent developments in Switzerland. Abstract Text: Professionalization of program development as an institutional responsibility In Switzerland, different developments in higher education have led to increased attention to the development and management of the study programs such as the Bologna process, an increasingly competitive environment, the tertiarisation of a number of professions formerly acquired through vocational education. Furthermore, the national qualification framework and in particular accreditation processes require HEI to demonstrate the effectiveness of their activities (e.g., Sursock & Smit, 2010). Many different actors have been involved in development processes on the program level but also within educational development units. However, so far a systematic discourse on key issues regarding the management and development of study programs is missing, not only in German-speaking Europe. The following main question will guide the round table session: How can educational development give vital impulses for program development? Our starting points are two approaches or frameworks from Swiss HEI: a) the definition of competencies for new program professionals at the Zurich University for Teacher Education and b) a process for the strategic development of didactically-aligned study programs at the University of St. Gallen. Framework 1: Competencies for program managers The experiences with a training program for study program managers at the Zurich University for Teacher Education are reported. Over a period of four years, a competency profile has been developed and refined. Insights into the challenges and struggles of this role were gained. Despite diverse job characteristics of program managers (often resulting from an institution-specific history), there is a common set of competencies necessary to successfully cope with organizational complexity such as role competency (Schein, 1992) and lateral leadership (Kühl et al., 2005). Framework 2: Towards a systematic development of study programs The second initiative concerns the strategic approach to program development implemented at the University of St. Gallen (Brahm & Jenert, 2013; Jenert, 2011). In this structured process, the program goes through four process steps: process initiation, program analysis, program development, evaluation of the process and results. A major challenge in this process is the role of program professionals. The goal is to establish them as change agents for a didactically-aligned study program. Outcome: Role of educational development After briefly introducing the two examples, the roles of program professionals and educational development in HEI will be discussed. The questions guiding the discussion will be: • How can program development be established as a continuing task, closely tied to quality development? • How can the competencies of program professionals be developed and the local capacity and ownership be strengthened? • How can educational development support program development and provide vital impulses? Audience Engagement. Depending on the number of participants, first the questions will be discussed in groups. To put the results of the discussion on record, it will be summarized and uploaded in our weblog for further discussion after the session.
Keywords: curriculum development; study programs; Bologna; educational development; higher education

Entwicklung der Motivation von Studierenden der Wirtschafts-wissenschaften im ersten Studienjahr-eine Mixed-Methods-Studie - Jenert, Tobias; Brahm, Taiga
Das erste Studienjahr wird als wesentlicher Übergang von der Schule in die Hochschule angesehen. Im Vordergrund steht dabei häufig die Fragen der Identitätsfindung der Studierenden und das "Ankommen" im neuen Lebensabschnitt (Briggs, Clark, & Hall, 2012; Scanlon, Rowling, & Weber, 2007). In diesem Zusammenhang werden ganz unterschiedliche Aspekte untersucht, z. B. die vorhandenen Lernkompetenzen oder das Zeitmanagement der Studierenden (Barron & D'Annunzio-Green, 2009), vorhandene Einführungsprogramme an Hochschulen (z.B. Gale & Parker, 2012) oder dem ‚student engagement‘ während des ersten Jahres (Krause & Coates, 2008). Obwohl die Motivation der Studierenden als starker Prädiktor für die Leistung angesehen wird (z. B. Busato, Prins, Elshouta, & Hamaker, 2000), wurde die Motivationsentwicklung im ersten Studienjahr bis dato nur selten betrachtet. Die vorliegende Mixed Methods-Studie setzt an dieser Forschungslücke an und untersucht die Entwicklung der Studienmotivation von Wirtschaftsstudierenden im Verlauf des ersten Studienjahres. Im Rahmen einer quantitativen Längsschnittuntersuchung mit drei Messzeitpunkten wird dabei die Motivationsentwicklung über die gesamte Studierendenpopulation hinweg erfasst. Im Mittelpunkt steht die Frage, wie sich die intrinsische und extrinsische Studienmotivation sowie die studienbezogene Selbstwirksamkeit über das erste Studienjahr verändern. Zudem wird untersucht, inwiefern verschiedene studienbezogene Variablen (z. B. Angst) sich auf die Motivationsentwicklung auswirken. Um vertiefte Erkenntnisse über die Bedeutsamkeit verschiedener Gestaltungsmerkmale des ersten Studienjahres auf die Motivationsentwicklung der Studierenden zu gewinnen, wurde parallel zur quantitativen Untersuchung eine qualitative Längsschnittstudie durchgeführt mit dem Ziel, (1) verschiedene Verläufe der Motivationsentwicklung und (2) kritische Ereignisse im Eingangsjahr zu identifizieren. Das vorliegende Papier zeigt in den folgenden beiden Kapiteln den theoretischen Bezugsrahmen der Studie und die methodische Vorgehensweise. Daraufhin werden die Ergebnisse sowohl der quantitativen als auch der qualitativen Studie dargestellt und im Rahmen der Diskussion miteinander verbunden.
Keywords: Motivationsentwicklung; Hochschule; motivation; Längsschnitt; Mixed Methods

Self-Regulation and Entrepreneurial Learning - Fust, Alexander; Jenert, Tobias
Research on entrepreneurial learning often stresses the role of experience and previous knowledge. We aim to advance this perspective by pointing out the prerequisites and limitations of experience-based forms of learning and by adapting findings from educational psychology to the entrepreneurial context. Developing a model of self-regulated entrepreneurial learning (SREL) we pursue a more process oriented view of entrepreneurial learning in order to explain how learning unfolds in contexts of uncertainty and novelty when relevant experience and knowledge are scarce. The model comprises a planning, a performance and a review phase in order to support entrepreneurs in their learning process. It is suggested how SREL is related to self-efficacy, emotions and cognitive biases.
Keywords: Unternehmertum; lernen

The crucial first year: The development of students' motivation at a Business School-a Mixed Methods Study - Brahm, Taiga; Jenert, Tobias
The transition from school to university can be overwhelming for some students. While students' motivation is considered a strong predictor of performance, the development of motivation during students' transition from high school to university has rarely been investigated. Additionally, little is known about the relation of motivational aspects with other influences on study performance. The present mixed methods study addresses this research gap and examines the development of economics students' study motivation. The longitudinal mixed-method study included three waves of data collected using quantitative surveys and a series of five interviews conducted with 14 first-year students over eight months. Regarding students' development over time, the quantitative analysis showed a gradual decline in students' motivation. However, in the interviews, certain events during the first year were identified as critical incidents demotivating students. These insights into the development of students' motivation at a business school show that concrete incidents influence students' motivational development; thus, they could be transformed by structural changes.
Keywords: motivation; business school; higher education; latent growth curve model; longitudinal study; mixed methods; interview; students

Transition within higher education institutions (HEI): Differences in learning culture (LC) between first-year, bachelor, and master students at a business school - Gebhardt, Anja; Jenert, Tobias
Tertiary education comprises at least two phases, undergraduate and graduate studies. Often, the first year is regarded another, crucial phase where students familiarize with the study environment. It can be hypothesized that students' individual perceptions of learning and studying as well as the pedagogies they experience differ depending on their current study phase. Yet, differences between the phases in HE have rarely been investigated. To capture differences in student experiences in HE comprehensively, Jenert and Gebhardt (2010) have developed a framework describing Learning Culture in HEI. LC comprises a number of constructs on the three levels of the individual student, pedagogical interactions and the organization. The study first aims to quantitatively describe differences in LC between the phases of HE within a university. Based on this analysis, a second goal is to develop a deeper understanding of how students manage the transitions between different phases by applying qualitative research methods.
Keywords: Higher Education; Transitions; Bachelor; Master

Wie kann über DBR die wissenschaftliche und praktische Relevanz der Forschung gesichert werden? - Brahm, Taiga; Jenert, Tobias
Auseinandersetzungen über Forschungsmethodologien haben in den Bildungswissenschaften lange Tradition. Sie werden häufig unversöhnlich und mit Profilierung der Gegensätze geführt. Für uns hängt die Sinnhaftigkeit einer Forschungskonzeption von der Problemstellung und dem Erkenntnisinteresse ab. Dies gilt auch für Design-Based Research (DBR). Dieser Ansatz entstand als Reaktion auf die Kritik an mangelnder praktischer Anwendung von Befunden aus der empirisch-analytischen Lehr-Lernforschung. Als Ergebnis werden Theorien angestrebt, die für die Praxis einen Nutzen bieten und zugleich über die Anwendung in einer singulären Situation hinausgehen. Wir wollen folgenden Fragen nachgehen: Wo liegen die Gemeinsamkeiten, wo die Spezifika von DBR gegenüber bestehenden Methodologien? Wie wird der Generalisierungsanspruch von Theorien innerhalb von DBR verstanden und umgesetzt? Für welche Erkenntnisinteressen eignet sich DBR? Welche Methoden sind für DBR sinnvoll und können wie angewendet werden?
Keywords: design-based research; gestatlungsbasierte Forschung; Erziehungswissenschaft; Design; Mixed Methods

Verändern Medien die Lernkultur? Mögliche Rollen von Technologie zwischen virtuellen und physischen Lernräumen - Jenert, Tobias (Lernumgebungen an der Hochschule. Auf dem Weg zum Campus von morgen)

Viel Neues und doch keine Innovation!?: Fünf Thesen, warum es die Lehrentwicklung an Hochschulen schwer ha - Jenert, Tobias

Change Management in Higher Education Institutions - Brahm, Taiga; Jenert, Tobias

Modelling long-range dependence and trends in duration series: an approach based on EFARIMA and ESEMIFAR models - Beran, Jan; Feng, Yuanhua; Ghosh, Sucharita (Statistical Papers)

On EFARIMA and ESEMIFAR Models - Beran, Jan; Feng, Yuanhua; Ghosh, Sucharita (Empirical Economic and Financial Research)

Double Conditional Smoothing of High-Frequency Volatility Surface Under a Spatial Model - Peitz, Christian; Feng, Yuanhua (Empirical Economic and Financial Research)

Data-driven estimation of diurnal patterns of durations between trades on financial markets - Feng, Yuanhua (Statistics & Probability Letters)

Data-driven estimation of realized kernels under dependent microstructure noise and further analysis using the Semi-FI-Log-ACD - Zhou, Chen; Feng, Yuanhua

Can the CCCTB Alleviate Tax Discrimination against Loss-Making European Multinational Groups? - Ortmann, Regina; Sureth-Sloane, Caren

Der Wandel wird zur Daueraufgabe - Sureth-Sloane, Caren (Frankfurter Allgemeine Zeitung)

Revenue and profit implications of industrial service strategies - Eggert, Andreas; Hogreve, Jens; Ulaga, Wolfgang; Muenkhoff, Eva (Journal of Service Research)

"Conceptual Model and Economic Experiments to Explain Nonpersistence and Enable Mechanism Designs Fosterin Behavioral Change" - Djawadi, Behnud Mir; Fahr, Rene; Turk, Florian (Value in Health)

The Wage Effects of Social Norms-Evidence of Deviations from Peers' Body Mass in Europe - Janssen, Elmar; Fahr, Rene

The internal market and the consumer: what consumers actually choose - Thommes, Kirsten; Faure, Michael; Heine, Klaus (Colum. J. Eur. L.)

The dark side of solidarity: social norms and social relations in the aftermath of strikes - Thommes, Kirsten; Akkerman, Agnes; Torenvlied, René; Born, Marieke (Industrial relations journal)

Kaufmännische Bildung? Sondierungen zu einer vernachlässigten Sinndimension

Wirtschaftspädagogische Handlungsfelder. Festschrift für Peter F. E. Sloane zum 60. Geburtstag

Berufsorientierung - Büchter, K.; Kremer, H.-Hugo; Zoyke, A. (bwp@ Berufs- und Wirtschaftspädagogik - online)

Embracing complex causality with the QCA method: An invitation - Schneider, M; Eggert, A (Journal of Business Market Management)

Differential effects of product and service innovations on the financial performance of industrial firms - Eggert, A; Thiesbrummel, C; Deutscher, C (Journal of Business Market Management)

Loyalitätswirkung des geschenkten bevorzugten Kundenstatus – Eine theoretische und empirisch-experimentelle Analyse

Der Übergang Bachelor - Master aus studentischer Perspektive: eine Rekonstruktion des Übergangshandelns als beruflicher Entwicklungspfad - Kremer, H.-Hugo; Rüschen, E. (bwp@ Berufs- und Wirtschaftspädagogik - online)

Individuelle Bildungsgangarbeit als Antwort auf Fachkräftebedarf und Qualifikationsveränderungen - Beutner, Marc; Zoyke, A (Arbeit der Zukunft – Zukunft der Arbeit)

Bildungsgangarbeit in beruflichen Schulen – Praxisphasen und ihre Auswirkungen in der Bildungsgangarbeit - Beutner, Marc (Wirtschaftspädagogische Handlungsfelder. Festschrift für Peter F. E. Sloane zum 60. Geburtstag)

E-Learning zur Sprach- und Berufsförderung – Einblicke in AGnovel. Advanced Graphic novels in der Beruflichen Bildung - Beutner, Marc; Fortmann, M; Pechuel, R (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Entrepreneurship und Berufliche Bildung: UMW – Under my Wing – Ein Innovationsprojekt zur Unterstützung von Absolventen aus nicht geschäftsbezogenen Disziplinen bei der Unternehmensgründung - Beutner, Marc; Fortmann, L. M. (Kölner Zeitschrift für Wirtschaft und Pädagogik)

On the Relation between Innovation and Competion: The Case of Energy Industry - Brummel, NinaMadeleine

Incorporating Reputation Information into Decision-Making Processes in Markets of Composed Services - Jungmann, Alexander; Brangewitz, Sonja; Petrlic, Ronald; Platenius, Marie Christin (International Journal On Advances in Intelligent Systems (IntSys))
One goal of service-oriented computing is to realize future markets of composed services. In such markets, service providers offer services that can be ﬂexibly combined with each other. However, although crucial for decision-making, market participants are usually not able to individually estimate the quality of traded services in advance. To overcome this problem, we present a conceptual design for a reputation system that collects and processes user feedback on transactions, and provides this information as a signal for quality to participants in the market. Based on our proposed concept, we describe the incorporation of reputation information into distinct decision-making processes that are crucial in such service markets. In this context, we present a fuzzy service matching approach that takes reputation information into account. Furthermore, we introduce an adaptive service composition approach, and investigate the impact of exchanging immediate user feedback by reputation information. Last but not least, we describe the importance of reputation information for economic decisions of different market participants. The overall output of this paper is a comprehensive view on managing and exploiting reputation information in markets of composed services using the example of On-The-Fly Computing.

Horizontale Fusionen: Theorie und Praxis am Beispiel zweier Entscheidungen des Bundeskartellamtes - Eusterholz, Fabian

Gender and ethnic discrimination in hiring : evidence from field experiments in the German labor market - Kolle, Andre
The present thesis investigates the prevalence of and the reasons for hiring discrimination against women and ethnic Turks in the German labor market. Subsequent to a discussion of how to reveal discrimination, the literature on wage and employment differences inside and outside the German labor market is reviewed. Afterwards, different (economic) theories explaining inequalities in labor markets are presented. In the empirical analyses a field experiment - the so called correspondence testing - is conducted where matched pairs of (fictitious) male and female as well as German-named and Turkish-named applicants respond to, respectively, 656 and 608 (real) apprenticeship offers in predominantly male-dominated jobs. Descriptive results and econometric analyses using probit regressions on various model specifications indicate that the female applicant has a 19 percent lower callback probability compared to her male counterpart. However, differential treatment is both job- and firm-type driven. While callback rates are not statistically different from zero in female-dominated and “gender-neutral” occupations, they prevail in jobs where men are overrepresented. Furthermore, discrimination is restricted to late recruiters, i.e., companies that advertise their vacancies right before the apprenticeship is supposed to start. Similar conclusions can be drawn from the study investigating ethnic discrimination. The 32 percent lower callback probability of the Turkish-named applicant decreases if early rather than late recruiters are addressed. Apart from that, comparing response and callback rates to the candidates using different experimental designs, i.e., sending out single versus pairs of applications, yields no statistically significant differences demonstrating the unbiasedness of the correspondence approach.

Die ökonomischen Auswirkungen der Kronzeugenregelung am Beispiel des Kaffeerösterkartells - Wemhöner, Vanessa

Decision Making under Asymmetric Information in Markets for Experience Goods: Empirical Evidence of Signaling Effects on Consumer Perceptions - Kaimann, Daniel

Vermögensteuer als Beitrag der Wohlhabenden für mehr Gleichheit - eine wirtschaftswissenschaftliche Betrachtung eines Steuerreformvorschlags - Sureth-Sloane, Caren (Wirtschaftspädagogische Handlungsfelder)

Effizienzmessung industrieller Dienstleistungen mittels Data Envelopment Analysis (ServDEA) - Backhaus, Klaus; Becker, Jörg; Beverungen, Daniel; Breuker, Dominic; Bröker, Ole; Alexander Brüne, Philipp; Dietrich, Hanns-Alexander; Knackstedt, Ralf; Peter Rauer, Hans; Reichle, Florian; Wilken, Robert (Produktivität von Dienstleistungen)

Zur Attraktivität von Advance Tax Rulings (ATRs) und Advance Pricing Agreements (APAs) für Investoren und Steuerbehörden: The Attractiveness of Advance Tax Rulings (ATRs) and Advance Pricing Agreements(APAs) for Investors and Tax Authorities - Kortebusch, Pia

Should Multinational Companies Request an Advance Pricing Agreement (APA) - Or Shouldn't They? - Kortebusch, Pia

Can Tax Rate Increases Foster Investment Under Entry and Exit Flexibility? - Insights from an Economic Experiment - Fahr, Rene; Janssen, Elmar A.; Sureth-Sloane, Caren

Do Investors Request Advance Tax Rulings to Alleviate Tax Risk (and do tax authorities provide them)? A Joint Taxpayers’ and Tax Authorities’ View on Investment Behavior - Diller, Markus; Kortebusch, Pia; Schneider, Georg; Sureth-Sloane, Caren

Boon or Bane? Advance Tax Rulings As a Measure to Mitigate Tax Uncertainty and Foster Investment - Diller, Markus; Kortebusch, Pia; Schneider, Georg; Sureth-Sloane, Caren

Gibt es eine optimale Frauenquote? - Gilroy, Bernard Michael; Heimann, Anastasia; Schopf, Mark (WiSt-Wirtschaftswissenschaftliches Studium)